The History Of The First International University In Uzbekistan (Zien Journal of Social Sciences and Humanities, 2025)
This article, using scientific literature, periodicals and Internet information, provides a comprehensive analysis of the establishment of the University of Westminster, the first in Central Asia and the Republic of Uzbekistan, the growing international status of this educational institution and role and prospects of the university in the development of education system in Uzbekistan